ANALISIS KESIAPAN GURU DALAM PELAKSANAAN KURIKULUM MERDEKA BELAJAR DI SD - Nofrianni, Elvima; Prahagia, Yelvia; Juwita Novalia, Ratih; Tri Susanti, Desi (Information Technology Education Department, 2024)
This research focuses on the importance of the curriculum in the learning process, considering that the curriculum is designed according to the needs in the field. The curriculum is defined as a series of plans and rules regarding objectives, material content, and teaching methods that act as a guide for organizing teaching and learning activities. The main objective of this study is to evaluate the extent to which teachers in primary schools are ready to implement the Merdeka Belajar Curriculum. The method used in this research is descriptive qualitative. The research subjects include teachers, principals, and vice principals in elementary schools. Data were collected through observation, interviews, and documentation. The results showed that the teachers in this school were ready and understood the Merdeka Belajar Curriculum, in accordance with various readiness indicators determined by the researcher. These indicators include understanding the curriculum structure, lesson plan preparation, learning process, teaching modules, and learning assessment. The results of this study show that teachers have been able to implement an independent curriculum with good teaching modules and media.